Perception of frontline employees towards career growth opportunities: Implications on turnover intention - Folakemi Ohunakin; Anthonia Adenike Adeniji; Olumuyiwa Oludayo; Omotayo Adewale Osibanjo (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
Retaining talented employees has become a major challenge confronting the management in hospitality industry. Researchers from different climes have advocated for adequate retention strategies such as career growth opportunities, for overcoming the alarming rate of employees' turnover in hotel organisations. However, there is paucity of empirical study on career growth opportunities and employees' turnover intention. To fill this gap, quantitative data were gathered with 327 copies of questionnaire, administered to the frontline employees working in twenty-two 5-star hotels in Nigeria. Structural equation modelling (SEM) was used to test the hypotheses, with descriptive statistics, path analysis, maximum likelihood estimates and goodness of fit indices. The results revealed that all the parameters for career growth opportunities used in this study, inversely interact with turnover intention among the respondents. The findings indicate that organisations should pay adequate attention to career goal progress, professional ability development, promotion speed and remuneration growth of their talented employees. It implies that, these factors are pivotal for saving the cost of hiring new entrants, reduce the rate of turnover intention/actual turnover, and retain experienced high performers in hotel industry. This research established the effects of career growth opportunities on turnover intention in Nigerian context.
Keywords: M1; M5; M52; 650; career growth; remuneration growth; career goal progress; professional ability development; promotion speed; employees' turnover intention